Legal Protection Against Violation of Song or Music Copyrights Based on Law Number 19 of 2002 Concerning Copyrights - Refi Monika (Trigin Publisher, 2022)
This research was conducted to find out the legal protection against copyright infringement of songs or music based on Law No. 19 of 2002 on copyright. The approach used in this study is a normative juridical approach, meaning that it examines statutory provisions while still addressing existing problems while examining their implementation in practice in the field. The results of this study a. Copyright protection is divided into two, namely preventive (by going through registration procedures) and repressive protection, namely protection provided in the event of a violation. These two aspects should not only be known in the form of a law, but also their contents and content must be understood; Copyright registration is intended as evidence in the event of a dispute and also as documentation to prevent abuse of rights; Completion of the law against works of copyright infringement of music can be done in 3 ways, namely: Criminal prosecution; Civilly, the copyright holder can file a claim for compensation to the Commercial Court; Settlement through arbitration or alternative dispute resolution through negotiation, conciliation mediation or other methods chosen by the parties in accordance with applicable laws.